Azeotropic pressure swing distillation of hydrochloric-water for hydrogen production in the CuCl cycle: Thermodynamic and design methods. (29th March 2019) - Farsi, Aida; Kayhan, Öznur; Zamfirescu, Calin; Dincer, Ibrahim; Naterer, Greg F.
Abstract: A pressure swing distillation (PSD) process is designed and analyzed in this paper for the maximum boiling azeotrope separation of an HCl-water binary mixture to recycle concentrated HCl (aq) within the CuCl cycle of thermochemical hydrogen production. Aspen Plus simulation and EES software are used to evaluate the characteristics of the PSD apparatus in terms of flow streams, thermodynamic properties and compositions in the binary azeotropic mixture. A heat transfer and mass transfer analysis (with the McCabe-Thiele method) are also used to predict the height of the packed bed distillation column. Results indicate that both analyses predict the same values for the low and high pressure packing column height of 1.7 m and 2 m, respectively. Due to the component's volatility changes through the azeotropic transition at the HCl-water separation, the minimum and maximum concentration of the HCl (aq) would be at the distillate ports of low and high pressure columns, respectively. Moreover, to break the azeotropic point of HCl (aq) in the PSD system, the minimum required low pressure feed concentration at the operating line slopes of 0.2, 0.4, 0.6 and 0.8 should be 0.086, 0.092, 0.097 and 0.103, respectively. From the results, the re-boiler and condenser heat duties at the high pressure distillation column are more affected with the change in the slope of the operating line, compared to the low pressure side. Highlights: A novel azeotropic pressure swing distillation of HCl(aq) for CuCl cycle is proposed. HCl (aq) thermodynamic properties and system flowsheet are provided from Aspen Plus simulation. Mass and heat transfer analyses are developed for distillation column height design. Minimum feed concentration is determined for a feasible azeotropic separation.